1997
DOI: 10.1063/1.474903
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on total and elastic cross sections for electron and positron scattering from CO2

Abstract: There remain discrepancies in the determination of the total and elastic cross sections for electron and positron collisions with carbon dioxide at impact energies from 0.3 to 100 eV. We have carried out a joint experimental and theoretical study in an attempt to resolve the differences. Our measurements for total cross sections for electron impact agree extremely well with those of Hoffman et al. ͓Phys. Rev. A 25, 1393 ͑1982͔͒ above 2 eV, while those for positron impact agree to better than 15% in magnitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…For specific inelastic processes, unfortunately, very few systematic studies by e 1 impact have been performed for gaseous targets, and a detailed comparative study between e 2 and e 1 impact is virtually nonexistent except for some preliminary investigation of experimental results for raregas atoms and simple molecules [2]. Only recently, Gianturco and colleagues [3(a)] have carried out a careful study on e 1 scattering from CO 2 molecule for elastic as well as vibrational excitation processes for the symmetric stretching mode, and have compared it with their previous study [3(b)] for e 2 scattering in order to shed some light on the coupling mechanism.Earlier in our study [4], we have observed that the total cross section for CO 2 for e 2 impact is indeed larger by 40% than that for e 1 impact below 100 eV or so, and continues to be so until the impact energy reaches down to 3 eV. Below 3 eV, however, the magnitude of the cross section is found to reverse, i.e., the total cross section for e 1 impact becomes larger by 25%, although it reverses again at much lower energy around 0.5 eV.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For specific inelastic processes, unfortunately, very few systematic studies by e 1 impact have been performed for gaseous targets, and a detailed comparative study between e 2 and e 1 impact is virtually nonexistent except for some preliminary investigation of experimental results for raregas atoms and simple molecules [2]. Only recently, Gianturco and colleagues [3(a)] have carried out a careful study on e 1 scattering from CO 2 molecule for elastic as well as vibrational excitation processes for the symmetric stretching mode, and have compared it with their previous study [3(b)] for e 2 scattering in order to shed some light on the coupling mechanism.Earlier in our study [4], we have observed that the total cross section for CO 2 for e 2 impact is indeed larger by 40% than that for e 1 impact below 100 eV or so, and continues to be so until the impact energy reaches down to 3 eV. Below 3 eV, however, the magnitude of the cross section is found to reverse, i.e., the total cross section for e 1 impact becomes larger by 25%, although it reverses again at much lower energy around 0.5 eV.…”
mentioning
confidence: 97%
“…Earlier in our study [4], we have observed that the total cross section for CO 2 for e 2 impact is indeed larger by 40% than that for e 1 impact below 100 eV or so, and continues to be so until the impact energy reaches down to 3 eV. Below 3 eV, however, the magnitude of the cross section is found to reverse, i.e., the total cross section for e 1 impact becomes larger by 25%, although it reverses again at much lower energy around 0.5 eV.…”
mentioning
confidence: 97%
“…The laboratory measured total scattering cross section (TCS) is available between 0.1 eV and 5000 eV. The TCS for e‐CO 2 collision has been measured by several authors in different energy ranges: Ferch et al [1981] in the energy range 0.007–4.5 eV, Buckman et al [1987] 0.1–5 eV, Szmytkowski et al [1987] 0.5–3000 eV, Kimura et al [1997] 0.8–500 eV, Kwan et al [1983] 1–500 eV, and Garcia and Manero [1996] 400–5000 eV. At low energies, the TCS of Szmytkowski et al [1987], Buckman et al [1987], and Ferch et al [1981] are in agreement to within 10%.…”
Section: Cross Sectionsmentioning
confidence: 99%
“…In the lowest energy range (<1 eV) Zecca et al [2002] adopted the experimental data of Ferch et al [1981] and Buckman et al [1987], which are in good agreement with each other. In the 1–1000 eV energy range, Zecca et al [2002] averaged the cross sections obtained by Szmytkowski et al [1987], Kimura et al [1997], and Kwan et al [1983], with equal weight, to obtain the recommended values, which are in good agreement with Garcia and Manero [1996] at higher (>400 eV) energies. In his review, Itikawa [2002] has recommended the TCS of Zecca et al [2002].…”
Section: Cross Sectionsmentioning
confidence: 99%
“…First measurements by Sueoka and collaborators [19] were performed down to 1 eV using 67.5 mm long scattering cell (we quote the geometrical length and not the "effective" 79.7 mm length) with 4 mm radius apertures and 9 G guiding field. The more recent data [20] (quoted also in [21]) were performed down to 0.3 eV with 1.8 G guiding field and 3 mm radius apertures; at 1 eV those data are by 10% lower than the value of Kwan et al [22] and 20% higher than the early set [19].…”
Section: Choice Of Experimental Datamentioning
confidence: 99%